Usefulness of PCR for diagnosing Meningococcal Septic Arthritis - Sylvain Raoul Simeni Njonnou; Muhammad Shahnawaz Soyfoo; Frederic-Alain Vandergheynst (Rheumatica Acta: Open Access - Peertechz Publications, 2019)
We report the case of a 60-year-old female patient who presented meningoencephalitis due to Neisseria meningitidis serogroup B in November 2018. She was admitted at the emergency department for febrile confusion lasting two days associated with one episode of vomiting. There was no visual disturbance, headache, photophobia or phonophobia. On physical examination, neck stiffness was observed but no other neurological focal sign was present. There was no cutaneous rash. Cerebral CT-scan was unremarkable.